Spatial and temporal analysis of meso- and microplastic pollution in the Ligurian and Tyrrhenian Seas. (October 2020) - Caldwell, Jessica; Muff, Livius F.; Pham, Christopher K.; Petri-Fink, Alke; Rothen-Rutishauser, Barbara; Lehner, Roman
Abstract: Areas like the Mediterranean coastlines, which have high population density, represent locations of high pollution risk for surrounding environments. Thus, this study aims to compare data on the abundance, size, and composition of buoyant plastic particles collected during two weeks in 2019 in the Ligurian and Tyrrhenian Seas with data from 2018. The results from 2019 show average meso- and microplastic particle concentrations of 255, 865 ± 841, 221 particles km −2, or 394.19 ± 760.87 g km −2 ; values which differ significantly from those reported in 2018. Microplastic particles accounted for 88.7% of the sample; the majority of which had a size range being between 1 and 2.5 mm. These data are an important milestone for long-term monitoring of the highly variable plastic pollution levels within this region; showing overlaps in zones of pollutant accumulation in addition to increased overall concentrations of plastic particles compared to previous data. Highlights: Average plastic particle concentrations were 255, 865 ± 841, 221 particles km -2, ranging from 1, 286 – 3, 814, 018 particles km -2 The average mass of the plastics collected was 394.19 ± 760.87 g km -2 with a range of 0.64 – 3, 298.40 g km -2 The average particle density for this 2019 study is 9 times higher than what was reported in the 2018 study Predominant polymer types were polyethylene (50.3%), polyamide (30.4%), polypropylene (10.9%), and polystyrene (1.9%) In 2019, the amount of polyamide increased 10% compared to polypropylene, which was found to have almost double the amount